Impact of pharmaceutical care on knowledge, quality of life and satisfaction of postmenopausal women with osteoporosis - Lai, P.S.; Chua, S.S.; Chan, S.P. (Springer Verlag, 2013)
BACKGROUND: This study describes the analysis of secondary outcomes from a previously published randomised controlled trial, which assessed the effects of pharmaceutical care on medication adherence, persistence and bone turnover markers. The main focus of this manuscript is the effect of the provision of pharmaceutical care on these secondary outcomes, and details on the design of the intervention provided, the osteoporosis care plan and materials used to deliver the intervention. OBJECTIVES: To evaluate the effects of pharmaceutical care on knowledge, quality of life (QOL) and satisfaction of postmenopausal osteoporotic women prescribed bisphosphonates, and their associating factors. SETTING: Randomised controlled trial, performed at an osteoporosis clinic of a tertiary hospital in Malaysia. METHODS: Postmenopausal women diagnosed with osteoporosis (T-score </=-2.5/lowtrauma fracture), just been prescribed weekly alendronate/risedronate were randomly allocated to receive intervention or standard care (controls). Intervention participants received a medication review, education on osteoporosis, risk factors, lifestyle modifications, goals of therapy, side effects and the importance of medication adherence at months 0, 3, 6 and 12. MAIN OUTCOMES MEASURE: Knowledge, QOL and satisfaction. RESULTS: A total of 198 postmenopausal osteoporotic women were recruited: intervention = 100 and control = 98. Intervention participants reported significantly higher knowledge scores at months 3 (72.50 vs. 62.50 ), 6 (75.00 vs. 65.00 ) and 12 (78.75 vs. 68.75 ) compared to control participants. QOL scores were also lower (which indicates better QOL) at months 3 (29.33 vs. 38.41), 6 (27.50 vs. 36.56) and 12 (27.53 vs. 37.56) compared to control participants. Similarly, satisfaction score was higher in intervention participants (93.67 vs. 84.83 ). More educated women, with back pain, who were provided pharmaceutical care had better knowledge levels. Similarly, older, more educated women, with previous falls and back pain tend to have poorer QOL, whilst women who exercised more frequently and were provided pharmaceutical care had better QOL. Satisfaction also increased as QOL increases and when provided pharmaceutical care. CONCLUSION: The provision of pharmaceutical care improved knowledge, QOL and satisfaction in Malaysian postmenopausal osteoporotic women, showing that pharmacists have the potential to improve patients' overall bone health. Policymakers should consider placing a clinical pharmacist in the osteoporosis clinic to provide counselling to improve these outcomes.